Analysis of Yeast Mold Contamination in Commercialized Chicken Sempol in Karanganyar District, Karanganyar Regency, Central Java - Ratnaduhita, Astari; Nurtanti, Ina; Wianto, Ardian Ozzy (Bantara Journal of Animal Science, 2023)
This research wants to find out if there is yeast mold in chicken sempol in Karanganyar Regency. The scientists used 10 chicken meat samples and a special kind of food for the bacteria to grow on. They also used water that had been purified. We did a study by watching how yeast mold grows, and then describing the results. The yeast mold test was done using the Total Plate Count (TPC) method. The samples were kept at a warm temperature for 7 days, and information was recorded on the 3rd, 5th, and 7th day. We compared the results with regulations from the Food and Drug Supervisory Agency (BPOM) No. In 2019, a new rule was made about how much yeast mold is allowed in processed meat. Please re-write this text using simpler words. The research found that samples A, B, and C had the most mold and yeast between the 3rd and 7th days of observation. At that time, sample G had the least amount of mold and yeast. Keywords:chicken sempol, yeast mold contamination, TPC.